2007
DOI: 10.1007/s11434-007-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically stress-regulated the expression of glutathione peroxidase 3 in Arabidopsis

Abstract: Gene expression of glutathione peroxidase 3 (ATGPX3) in response to osmotic stress was analyzed inArabidopsis using ATGPX3 promoter-glucuronidase (GUS) transgenic plants. High levels of GUS expression were detected under osmotic stress in ATGPX3 promoter-GUS transgenic plants. Compared with the wild type, the growth and development of ATGPX3 mutants (atgpx3-1) were more sensitive to mannitol. In addition, the expression of RD29A, ABI1, ABI2 and RbohD in atgpx3-1 was induced by ABA stress. These results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Of the various antioxidant enzymes, GPX and CAT represent the principal ROS scavengers in plants. In recent years, increasing evidence has been found that GPX in plants plays an important role in regulating plant responses to various abiotic stresses such as salt, drought, heat, cold, and oxidative stress [106][107][108][109][110][111]. In most cases, as with other antioxidant enzymes, the levels of functional GPX in the cell increases consistently.…”
Section: Glutathione Peroxidase (Gpx)mentioning
confidence: 99%
“…Of the various antioxidant enzymes, GPX and CAT represent the principal ROS scavengers in plants. In recent years, increasing evidence has been found that GPX in plants plays an important role in regulating plant responses to various abiotic stresses such as salt, drought, heat, cold, and oxidative stress [106][107][108][109][110][111]. In most cases, as with other antioxidant enzymes, the levels of functional GPX in the cell increases consistently.…”
Section: Glutathione Peroxidase (Gpx)mentioning
confidence: 99%
“…, ; Miao et al . ). The same phenomenon was also observed in Salvia miltiorrhiza (Han ), perennial ryegrass ( Lolium perenne L.) (Hu et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Miao et al . ). GPx mRNA also increased in the tissues of several plant species undergoing stress including salt stress in suspension cells, cold stress, light stress and heavy metal poisoning (Avsian‐Kretchmer et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations